Establishing the safety and efficacy of an opioid titration protocol - Wells, DNSc, RN, Nancy; Murphy, MD, Barbara; Douglas, MSN, RN, Stacey; Yelton, MSN, RN, Nancy (Journal of Opioid Management, 2005)
The primary goal of this single-group study was to determine the safety of a standard opioid titration order sheet to manage pain in ambulatory cancer patients. Secondary goals were to examine opioid toxicity and efficacy of this pain protocol. Twenty-seven patients who required fixed-dose opioids and who had uncontrolled pain were enrolled. All patients had their initial opioid dose titrated by the study physician using the opioid titration order sheet. Data were obtained by the study nurse during a weekly telephone interview and used to determine if pain was controlled. After initial titration, a trained study nurse titrated opioid doses based upon the standing order sheet. At each contact, patients were assessed for adverse effects, pain intensity, and analgesics used. Patients who completed the four-week trial (n = 17) did not differ from patients who did not complete the trial. No adverse effects were observed in 39 opioid titrations com-pleted by the study nurse. Opioid toxicities, worst pain, usual pain, and pain-related distress declined from baseline to week four. Patients who were adherent to their prescribed medications reported significantly lower pain intensity and distress (ps < 0.06). The opioid titration order sheet, used by a trained nurse, is safe to use in ambulatory cancer patients who have moderate to severe pain. Common opioid toxicities were reduced. The protocol also demonstrated initial efficacy in improving worst and usual pain and pain-related distress. Further research to establish efficacy of theprotocol is recommended.